Manejo de sigatoka negra mycosphaerella fijiensis en banano,en dos sistemas de siembra: alta densidad y convencional en la provincia de El Oro - Valarezo Malla, Jonathan Renán (2012)
The trial was conducted in the months of May, 2011 to February 2012, the farm was located in Santa Barbara in the canton And Change Machala, El Oro province research was conducted in three hybrids Williams, Gall, Jaffa and two densities high density and low density, on the progress of black Sigatoka infection by the method of biological Advance notice and method of Stover, which was raised for the following objectives:1. Measuring the evolutionary stage of the disease in high-density system with 1900 plants per hectare, and low density 1450 plants per hectare.2. Evaluate the effectiveness of disease control black Sigatoka meristems with two planting systems.3. Perform an economic analysis of this study.Early detection of symptoms of the four youngest leaves of the plant was performed on 10 young plants per plot per hybrid, in the case of the hybrid Williams established an additional plot for the case of the high density of plants / has. In the method of Stover took 5 floors ewes and proceeded to the observation of the number of spots for classifying the degrees of Stover.The data were collected weekly, the densities of attack also noted with reference to an amount of 50 lesions developed symptom. It was noted with the plus (+) and minus (-), depending on whether or not exceed that value. Assessments should be done at fixed intervals of seven days to the extent possible, on the same plants.The seeding density influenced the growth of disease infection in the hybrid Willams high density was higher in the first control cycles, declining in proximity to flowering plants.The severity of the disease under control system supported by the rotation of fungicides chlorothalonil, Timorex, serenade, cocktails with mancozeb shorter times required to maintain control the infection under control.The high density of plants per hectare, favored the growth of black Sigatoka infection compared to low density.The methodology used in the low density Williams gave positive results in the field and financially, at a cost of 4396.08 dollars per hectare.